2021
DOI: 10.1021/acsengineeringau.1c00021
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Hybrid Route to Renewable Methacrylic Acid via Biomass-Derived Citramalate

Abstract: Scheme 1. Hybrid fermentation and thermocatalysis to produce Methacrylic acid (MAA) from glucose through citramalic acid.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Citramalate and 2-methylsuccinate are synthesized through the citramalate pathway using pyruvate and acetyl-CoA as starting materials. Citramalate, an organic compound, has the potential to serve as a precursor for methacrylate (MA), a crucial component in the production of polymers such as poly­(methyl methacrylate) (PMMA) and styrene-methyl methacrylate (SMMA). , The use of biobased citramalate in the hybrid approach for MA synthesis has garnered significant attention due to its advantages over conventional chemical methods, primarily in terms of avoiding the formation of hazardous byproducts. , …”
Section: Overview Of C4 and C5 Dcasmentioning
confidence: 99%
See 1 more Smart Citation
“…Citramalate and 2-methylsuccinate are synthesized through the citramalate pathway using pyruvate and acetyl-CoA as starting materials. Citramalate, an organic compound, has the potential to serve as a precursor for methacrylate (MA), a crucial component in the production of polymers such as poly­(methyl methacrylate) (PMMA) and styrene-methyl methacrylate (SMMA). , The use of biobased citramalate in the hybrid approach for MA synthesis has garnered significant attention due to its advantages over conventional chemical methods, primarily in terms of avoiding the formation of hazardous byproducts. , …”
Section: Overview Of C4 and C5 Dcasmentioning
confidence: 99%
“…60,61 The use of biobased citramalate in the hybrid approach for MA synthesis has garnered significant attention due to its advantages over conventional chemical methods, primarily in terms of avoiding the formation of hazardous byproducts. 62,63 In contrast, 2-methylsuccinate has various applications in the pharmaceutical industry and the production of biodegradable plastics. 64−66 Due to the harsh conditions and high costs associated with chemical synthesis, there has been a growing interest in exploring biobased approaches for its production.…”
Section: C4 and C5mentioning
confidence: 99%
“…The sensor was proved to be remarkably selective and efficient. Significantly, considering that it has been recently demonstrated that it is possible to produce MAA from biomass-derived glucose, the manufacturing of this sensor can be considered potentially sustainable, as summarized in Figure 5 [ 113 ].…”
Section: Section A: Environmental Analysismentioning
confidence: 99%
“…[23][24][25][26][27] Another underutilized alkenoic acid is citraconic acid (V), mostly formed by isomerization of itaconic acid. [28][29][30][31][32] Unsaturated acids I-V are important in view of the possible derivatization of the C=C double bond to forge new CÀ C bonds. One of the most eco-sustainable approaches for the derivatization of biomass-derived compounds is through the implementation of photochemical/photocatalyzed strategies, [33] making use of traceless photons.…”
Section: Introductionmentioning
confidence: 99%
“…However, this acid may be also obtained by fungal fermentation (employing Rhizopus strains) of starch‐containing materials, glucose, xylose and lignocellulosic derivatives [23–27] . Another underutilized alkenoic acid is citraconic acid ( V ), mostly formed by isomerization of itaconic acid [28–32] …”
Section: Introductionmentioning
confidence: 99%